2003
DOI: 10.1210/en.2002-0115
|View full text |Cite
|
Sign up to set email alerts
|

Arcuate Nucleus-Specific Leptin Receptor Gene Therapy Attenuates the Obesity Phenotype of Koletsky (fak/fak) Rats

Abstract: Leptin signaling in the hypothalamic arcuate nucleus (ARC) is hypothesized to play an important role in energy homeostasis. To investigate whether leptin signaling limited to this brain area is sufficient to reduce food intake and body weight, we used adenoviral gene therapy to express the signaling isoform of the leptin receptor, lepr(b), in the ARC of leptin receptor-deficient Koletsky (fa(k)/fa(k)) rats. Successful expression of adenovirus containing lepr(b) (Ad-lepr(b)) selectively in the ARC was documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
104
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(112 citation statements)
references
References 45 publications
7
104
1
Order By: Relevance
“…LEP is anorexigenic in mammals, and this central action of LEP on appetite and energy balance is mediated through the dorsomedial, ventromedial, ventral premamillary and arcuate nuclei (ARC) of the mediobasal hypothalamus, where the full-length functional LEP receptor (LEPRb) is highly expressed (Elmquist et al 1998, Morton et al 2003. In the ARC, LEP inhibits the gene expression of the orexigenic neuropeptide Y (NPY) and agouti-related peptide (AGRP), and stimulates the expression of the anorexigenic proopiomelanocortin (POMC) and cocaine-and amphetamine-regulated transcript (CART) (Kristensen et al 1998, Bates et al 2003, Morrison et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…LEP is anorexigenic in mammals, and this central action of LEP on appetite and energy balance is mediated through the dorsomedial, ventromedial, ventral premamillary and arcuate nuclei (ARC) of the mediobasal hypothalamus, where the full-length functional LEP receptor (LEPRb) is highly expressed (Elmquist et al 1998, Morton et al 2003. In the ARC, LEP inhibits the gene expression of the orexigenic neuropeptide Y (NPY) and agouti-related peptide (AGRP), and stimulates the expression of the anorexigenic proopiomelanocortin (POMC) and cocaine-and amphetamine-regulated transcript (CART) (Kristensen et al 1998, Bates et al 2003, Morrison et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Leptin receptors are expressed in the ARH (Elmquist et al, 1998a) and it contains high densities of neurons that express Fos protein and SOCS-3 mRNA after intravenous injection of leptin (Elias et al, 1998(Elias et al, , 2000Elmquist et al, 1998b). Lesions of the ARH result in leptin insensitivity (Choi et al, 1999), and viral transfection of leptin receptor into ARH neurons alone is sufficient to cause reductions in food intake in leptin receptor-deficient rats (Morton et al, 2003). From the ARH, leptin signals appear to be distributed through neural projections to other sites implicated in the control of feeding, such as the paraventricular nucleus of the hypothalamus (PVH), the dorsomedial hypothalamic nucleus (DMH), and the lateral hypothalamic area (LHA) (Elias et al, 1998Elmquist et al, 1998b).…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of leptin receptors in the CNS recapitulates the effects of leptin deficiency on metabolic homeostasis (6). In addition, several studies have found that selective perturbation of leptin action within populations of medial basal hypothalamic neurons accounts for some of the effects of leptin in the regulation of energy balance (7)(8)(9)(10)(11). For example, leptin receptor deletion in proopioid melanocortin (POMC) arcuate neurons and steroidogenic factor 1 neurons in the ventromedial hypothalamus (VMH) produces modest obesity (7,10).…”
Section: Introductionmentioning
confidence: 99%